Medication adherence among the elderly: applying grounded theory approach in a developing country - Peivand Bastani; Parisa Bikineh; Gholamhossein Mehralian; Omid Sadeghkhani; Rita Rezaee; Zahra Kavosi; Ramin Ravangard (Taylor & Francis Group, 2021)
Background Medication adherence is an important concept particularly among the elderly that can, directly and indirectly, affect the health system's costs and the elderly's health, quality of life, and functional abilities. This study aimed to determine the model of medication adherence among the Iranian elderly using the grounded theory approach. Methods The concept of medication adherence and the determination of its process among the elderly is a multidisciplinary social issue that can be affected by many contextual factors. Grounded theory with the approach of Strauss and Corbin (2004) was applied to determine the customized model. Data triangulation occurred through semi-structured interviews, observation, field notes, and memoing. Open coding, selective coding, and axial coding were applied to analyze the data. Results Delinquency in the medication use among the elderly was caused by factors such as doubtfulness, fear of complications, not following the patients by the physicians, and negative others and medical staff's impacts. During the process of medication adherence, the patient's lack of knowledge, lack of sufficient education, inappropriate and restricted lifestyle, difficult living conditions, and social pressures imposed on individuals could exacerbate and worsen the delinquency in medication adherence. It should not be neglected that some other factors such as lack of an effective supervision system, lack of supportive organizations, stakeholders' market-based behaviors, consumption inconvenience, consumption stress, hopelessness, and misunderstanding could also aggravate the delinquency. Conclusions Although the proposed theory and model were customized and context-based for the Iranian elderly, in general, making positive changes in the process of adherence to the medication use among the elderly requires scientific and basic management and planning of its factors. It should be noted that making these changes requires some interventions in and cooperation of all levels of the country's health system, from the Ministry of Health and Medical Education to the individual level of the elderly.